1998
DOI: 10.1111/j.1532-5415.1998.tb04535.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise to Improve Spinal Flexibility and Function for People with Parkinson's Disease: A Randomized, Controlled Trial

Abstract: Study results demonstrate that improvements in axial mobility and physical performance can be achieved with a 10-week exercise program for people in the early and midstages of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
1
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(141 citation statements)
references
References 26 publications
(46 reference statements)
5
130
1
3
Order By: Relevance
“…105 Examples of possibly useful interventions include the use of cueing, 33,106 teaching of alternative motor strategies to make safer transfers, 107 gait training with external weight support, 108 and the use of exercises to improve stability, spinal flexibility, and general fitness. 64,109 Patients with FOG should be taught not to try and overcome their motor block during walking, as this may increase the risk of a fall. Physiotherapy is best delivered in the domestic situation, as the effects of home treatment exceeded those of hospital-based interventions.…”
Section: Physiotherapymentioning
confidence: 99%
“…105 Examples of possibly useful interventions include the use of cueing, 33,106 teaching of alternative motor strategies to make safer transfers, 107 gait training with external weight support, 108 and the use of exercises to improve stability, spinal flexibility, and general fitness. 64,109 Patients with FOG should be taught not to try and overcome their motor block during walking, as this may increase the risk of a fall. Physiotherapy is best delivered in the domestic situation, as the effects of home treatment exceeded those of hospital-based interventions.…”
Section: Physiotherapymentioning
confidence: 99%
“…Musculoskeletal exercises are sometimes used concurrently with strategy training in people with PD 53,54 and aim to improve strength, joint range of movement, endurance, and general mobility. No trials have yet been reported on the direct effects of musculoskeletal exercises on freezing of gait in people with PD.…”
Section: Gait Rehabilitation Strategies To Reduce Freezingmentioning
confidence: 99%
“…Although there is increasing evidence that well-focused physiotherapy can improve the patients' quality of life, there is no general consensus on the type of rehabilitation program most useful for patients with PD [5]. Moreover, most clinical trials of physical therapy in PD were based on short-term rehabilitation programs [3,14,17], and usually the improvements were not maintained after the physical therapy phase [3,17].…”
Section: Introductionmentioning
confidence: 99%